THE COMPARISON OF THE INDONESIAN PPATK ROLE WITH OTHER COUNTIES FINANCIAL INTTELLIGENCE (FIU) - Rosidah, Nikmah (JURNAL KOMPILASI)
Today the fight against international money laundering activities, even in many countries and on regional basis it has become one of the political agenda that is always discussed. Some of the things that drive a number of govemments to combat money laundering especially is a concern of organized crime that the result so far untouched by the applicable laws and regulations, in addition to the international pressure on countries that have not implemented anti-money laundering regime completely as experienced by Indonesia and other countries